Short term topological changes of coronal holes associated with prominence eruptions and subsequent CMEs - Gutiérrez Garro, Heidy (2013)
We study the short-term topological changes of equatorial and polar coronal hole (CH) boundaries, such as a variation of their area and disintegration, associated to reconnection with nearby (within 15° distance) quiescent prominence magnetic ﬁelds leading to eruptions and subsequent Coronal Mass Ejections (CMEs). The examples presented here correspond to the recent solar minimum years 2008 and 2009. We consider a temporal window of one day between the CH topological changes and the start and end times of prominence eruptions and onset of CMEs. To establish this association we took into account observational conditions related to the instability of prominence/ﬁlaments, the occurrence of a CME, as well as the subsequent evolution after the CME. We found an association between short-term local topological changes in CH boundaries and the formation/disappearance of bright points near them, as well as, between short-term topological changes within the whole CH and eruptions of nearby quiescent prominences followed by the appearance of one or more CMEs.